The Features and Problems of Management and Oversight of State-owned Enterprises and Sover-eign Funds in the RA - Tevosyan, Sargis (Bulletin of Yerevan University G: Economics, 2024)
The article discusses the role of state-owned joint stock companies in the country's economy and financial system. Analyzing the viewpoints of a number of famous economists, a number of problems typical for effective SOE management were raised. The role of SOEs has been considered by three separate viewpoint. In one case as they considered as bodies that pay dividends to the state budget and provide state budget revenues and in the other case as bodies active within the framework of state policy in areas where private participation is not possible to achieve the stated goals of the state. In addition, in terms of state funds, SOEs were considered as entities providing financial flows in the form of investments in the economy. In the article, the problems and possible risks of the SOE management process in RA were identified and classified in the mentioned cases, as well as innovative proposals for their solution were presented. Compilations of statistical data on state-owned companies in foreign countries have been carried out.Management challenges, financial processes, operational efficiency and productivity, transparency and accountability, legislative, political, social economic and other issues discussed in the system approach were highlighted in the process of managing the state share of SOEs.
Keywords: state-owned enterprise; strategic management; sovereign funds; privatization; nationalization; government intervention; governance challenges; accountability; transparency; operational efficiency; corruption; socioeconomic impact